IDENTIFICATION OF LAND CHARACTERISTICS IN DRAGON FRUITS PLANTS (Hylocerreus undatus) - Gonzaga, Natalis Rahmat; Hazriani, Rini; Gunawan, Joni (Fakultas Pertanian Universitas Tanjungpura, 2018)
This study aims to identify land characteristics (soil physical characteristics and soil chemistry). Identifying land characteristics for dragon fruit plants (Hylocerreus undatus) and explaining land characteristics based on soil and plant observation parameters.This research was conducted in Purun Besar Village, Segedong District, Mempawah Regency. Then followed by conducting soil analysis at Soil Chemistry and Soil Fertility Laboratory, Soil Physics and Soil Conservation Faculty of Agriculture, Tanjungpura University Pontianak. The research method starts from preparation, field survey, soil analysis in the laboratory, data interpretation, and presentation of results. The parameters observed in this study are divided into 2 parts: field observation and laboratory analysis. Parameters in the field are groundwater depth (cm), rooting medium, soil maturity, soil structure, sulfidic depth, surface rock and rock outcrop. The parameters in the laboratory are C-Organic (%), Cation Exchange Capacity (cmol (+) kg-1), N-Total (%), P content available (ppm), K-dd content (cmol (+) kg-1 ), soil reaction (pH), Al saturation, salinity, soil texture, plant height, number of branches in stem and data processing and potential land analysis. Keywords: Land Characteristics. Dragon fruit